Peran Nilai-nilai Pendidikan Agama Islam dalam Pendidikan Mitigasi dan Adaptasi Perubahan Iklim - Ach Munfaridji Aziz; Lisa Aryani; Leni Rismawati (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2025)
Climate change is a global challenge with significant impacts on environmental, social, and economic sustainability. Education is a crucial instrument in raising public awareness and preparedness in facing the risks of climate change. In this context, Islamic Religious Education (PAI) plays a strategic role through the instillation of Islamic values, which emphasize the importance of maintaining the balance of nature, human responsibility as caliphs, and spiritually based ecological ethics. This literature study aims to analyze the contribution of PAI values ​​to climate change mitigation and adaptation education. The research method uses a literature review by examining relevant sources such as scientific journals, books, and Islamic education policy documents. The results of the study indicate that Islamic values ​​such as amanah (trust), tawazun (balance), ihsan (goodness), and the prohibition of facade (destruction) are directly relevant to climate change mitigation efforts through reducing consumer behavior, strengthening conservation ethics, and sustainable resource management. Meanwhile, in the context of adaptation, PAI can strengthen community resilience through disaster awareness education, social empathy, and humanitarian solidarity in response to climate risk. Integrating Islamic Religious Education (PAI) values ​​into project-based learning, eco-friendly curricula, and green school programs has the potential to improve students' climate literacy. In conclusion, PAI holds significant potential for building ecological awareness and adaptive behavior through the internalization of Islamic values, thereby supporting community resilience in the face of climate change.